Spatiotemporal heterogeneity of driving factors of carbon emission efficiency in industrial parks: evidence from China’s national high-tech zones - Li, Chunling; Han, Jun (Frontiers in Environmental Science, 2025)
Industrial parks serve as the core spatial units of global manufacturing and energy consumption, and their low-carbon transformation plays a critical role in achieving the “dual-carbon” goals. This study employs a non-oriented Super Slack-Based Measure model under the assumption of non-increasing returns to scale to measure the carbon emission efficiency of 178 national high-tech zones in China from 2008 to 2023. Within the framework of eight integrated economic regions, regional comparison, efficiency rating, and industrial-combination analyses are conducted. The Moran Index is applied to test spatial autocorrelation, while the Geographical Detector and the Multiscale Geographically and Temporally Weighted Regression model are used to analyze the explanatory power and spatiotemporal heterogeneity of driving factors across four dimensions: economic development and industrial structure, technological innovation and research and development, environmental policy and green finance, and human and social development. The results reveal that carbon emission efficiency shows a spatial pattern characterized by higher values in the south and coastal areas and lower values in the west and inland regions. High-efficiency industrial combinations exhibit synergistic enhancement effects, whereas low-efficiency combinations experience efficiency losses. Overall efficiency displays a spatially negative correlation, indicating insufficient diffusion of low-carbon technologies and a noticeable “siphon effect” among neighboring zones. Among endogenous factors, park area and carbon emissions per unit of industrial output are the dominant driving forces, while exogenous factors play a relatively limited role. Variables at the local scale demonstrate high heterogeneity and short response times, suggesting that expanding production capacity should be accompanied by technological progress and the efficient allocation of land and capital to reduce carbon emissions per unit of output. On this basis, differentiated emission-reduction pathways can be designed to promote the coordinated advancement of economic growth and low-carbon transformation.